Development of a Sales Information System Using MicrosoftAccess at PT Wings Group to Improve the Effectiveness of Goodsand Transaction Data Management - Iklima Al Aura Amarulloh; Sahlaa Azizaah Julianda Julianda (Records Management System Journal, 2025)
PT Wings Group, as a company in the Fast Moving Consumer Goods (FMCG) sector, has complex sales and distribution activities, requiring an accurate and integrated information system. This study aims to develop a sales information system using Microsoft Access as a solution for managing product, customer, and transaction data, which was previously done manually. The development method used is the Waterfall model, which includes requirement analysis, design, implementation, testing, and system maintenance. Data was obtained from internal company documents and relevant literature. The development results show that this system can simplify recording processes, accelerate transaction calculations, and generate reports automatically. With this system, PT Wings Group can improve efficiency and accuracy in its daily sales processes.